PENGARUH PENERAPAN BAURAN PEMASARAN TERHADAP VOLUME PENJUALAN ROTI AROMA BAKERY - Vimandita, Anggun; Bahrun, Khairul (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2021)
This study aimed to find out the effect of marketing mix consisting of product, price, place, promotion toward sales volume of Aroma Bakery on Jl. Bhayangkara Bengkulu City. This research was a quantitative study with a sample of 96 respondents by using accidental sampling techniques. The data collection techniques of this study used observation and questionnaire. The data analysis techniques of this study used descriptive analysis, classical assumption testing, multiple linear regression analysis techniques, coefficient of determination (R2) analysis, and hypothesis testing. The results of this study indicate that from multiple linear regression tests by using SPSS i.e. Y = 3.050 + 0.922 (X1) + 0.287 (X2) + 0.223 (X3) + 0.367 (X4), as well as the coefficient of determination R2 = 0.797 which means Product (X1), Price (X2), Place (X3), and Promotion (X4) contributed an effect of 79.7% toward sales volume and 20.3% determined by other factors outside of this study. From the partial hypothesis test result (T Test) that the Product (X1) has a significant effect toward the sales volume of Aroma Bakery in Bengkulu City, by showing a significance value of 0.000 < 0.050. Price (X2) has a significant effect toward the sales volume of Â Aroma Bakery in Bengkulu by showing a significance value of 0.026 < 0.050. Place (X3) has a significant effect toward the sales volume of Aroma Bakery in Bengkulu City, by showing a significance value of 0.025 < 0.050. The promotion (X4) significantly effect toward the sales volume ofÂ  Aroma Bakery in Bengkulu by showing a significance value of 0.012 < 0.050. From the results of the hypothesis simultaneously (Test F) shows a significance value of .000 < 0.050 thus Ho rejected Ha received. This means that together product, price, place, and promotion have a significant effect both partially and simultaneously toward the sales volume of Aroma Bakery on Jl. Bhayangkara Bengkulu City.Keywords : Marketing Mix and Sales Volume.